Successful retrograde transvenous obliteration for splenorenal shunts after liver ransplantation: Midterm results - Wang, Hao; Gao, Haijun; Chen, Guang; Yi, Zhengjia (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The objective of this study was to evaluate the use of Amplatzer-assisted retrograde transvenous obliteration (RTO) in patients with splenorenal shunts (SRSs) after orthotopic liver transplantation (OLT). Materials and Methods: From August 2015 to March 2017, 5 patients received RTO at our center because of SRSs after OLT. The clinical features of the patients with SRSs included demographics, donor type, new-onset symptoms, liver function tests, imaging examinations, interventional examinations and treatments, and outcomes. The patients who received RTO were regularly monitored, and data were gathered before and after the procedures and compared using the paired-sample t test. Results: Percutaneous interventional management was successfully undertaken in all patients, and 5 Amplatzers and 2 stents were also implanted successfully in patients owing to portal vein (PV) stenosis. There were no procedure-related complications in these patients. In all 5 patients with SRSs, 2 weeks after the interventional therapy, the computed tomography findings showed that the splenic renal shunt vein was completely blocked. The mean blood pressure in the donor lateral PV and the mean blood flow velocity of the donor lateral PV after RTO were all improved significantly (p<0.05). It also suggested that all 5 patients with SRSs survived, with the primary graft functioning normally at the final follow-up. Conclusion: Amplatzer-assisted RTO is a safe and effective treatment for SRSs after OLT. Considering the complexity of the diagnosis and treatment of SRSs in liver transplantation, this complication should be taken seriously.